Proximal-type epithelioid sarcoma in pubic region expressing L-type amino acid transporter 1: A case report. (January 2022) - Yahiro, Shunsuke; Fujimoto, Takuya; Fujita, Ikuo; Takai, Toshihiro; Sakuma, Toshiko; Sudo, Tamotsu; Morishita, Masayuki; Takigami, Shunsaku; Kawamoto, Teruya; Hara, Hitomi; Akisue, Toshihiro; Kuroda, Ryosuke; et al.
Proximal-type epithelioid sarcoma is an aggressive malignant soft-tissue neoplasm, a "proximal" variant of epithelioid sarcoma, resistant to multimodal therapy and involved in early tumor-related death. Pertinent treatments are, therefore, continually being explored. A 24-year-old woman with nonmetastatic proximal-type epithelioid sarcoma, originating subcutaneously on the right side of the vulva, underwent surgical resection; the lesion recurred, however, leading to death 3 months after the second surgery. Here described is a case of proximal-type epithelioid sarcoma expressing L-type amino acid transporter 1 (LAT1) that transports essential amino acids and p -borono-L-phenylalanine (BPA)— the chemical compound used in boron neutron capture therapy (BNCT)—and is highly expressed in many malignant tumors. Recently, LAT1 has drawn attention, and relevant treatments have been studied—LAT1 inhibitor and BNCT. LAT1 expression in proximal-type epithelioid sarcoma may lead to cogent treatments for the disease.